The ecology and the adaptation of Taiwan's public administration - Wen-Shien Peng (1995)
Since moving its seat to Taiwan in 1949, the Government of the Republic of China had been able to resume its efforts on this island with a quickening speed. Owing to rapid political, economic, and social development in the past decades, Taiwan's administrative environment is quite different from what it was. Transforming from a continent to an island, national to local, and agriculture to industrialization, the public's demands have differed greatly. In order to affect the modernization of Taiwan's economy and keep it developing and maturing, to rely on those experts trained in rationalized organization theory and modernization management is imperative. In this paper, I will try to demonstrate the ecological background of modern Taiwan's social structure and the necessity of adapting Western managerial theory and skill to Taiwan's public administration. - Reproduced
Keywords: Public administration - Taiwan; Public administration